Effect of Vitamin A and Magnesium Supplementation on Protein Consumption and Nitrogen Retention of Sheep - Tsany, Muhammad Iqbal Rizqi; Suryapratama, Wardhana; Suhartati, Fransisca Maria (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
The research aimed to examine the effect of vitamin A and magnesium supplementation on protein consumption and nitrogen retention in sheep was carried out on February 29 - June 26 2023. The material used was 18 local male sheep aged 7 - 8 months with a weight of 17,12 ±1,94 kg were reared for 2 months in individual stage model cages. The basal feed given is concentrate (75%) and ammoniated rice straw (25%). The in vivo experimental method uses a Randomized Complete Block Design (RCBD) as a group, namely the initial weight of the research sheep, consisting of 6 groups that act as repeaters. Treatments tested T1 = Ammoniated rice straw (25%) + concentrate feed (75%); T2 = T1 + vitamin A (2000 IU); T3 = T2 + magnesium mineral (1 gram). The variables measured were protein consumption and nitrogen retention. The data obtained was then analyzed using analysis of variance (ANOVA) which was further tested with the Honestly Significant Difference (HSD) test. Protein consumption was significantly influenced by treatment (P<0.05) with a mean of 101.71 ± 3.85 grams/head/day (T1), 109.03 ± 8.60 grams/head/day (T2), and 115.99 ± 5.35 grams/head/day (T3). Likewise, nitrogen retention was significantly influenced by treatment (T<0.05) with an average of 9.37 ± 1.41 grams/head/day (T1), 9.81 ± 1.51 grams/head/day (T2), 10.21 ± 1.53 grams/head/day (T3). The HSD test results showed that the protein consumption and nitrogen retention of T3 sheep were significantly (P<0.05) higher than those of T1 and T2. The research conclusion was that supplementation of vitamin A and magnesium (T3) in basal feed was able to increase protein consumption by 12.31% and nitrogen retention by 8.24% in sheep when compared to the control treatment (T1).